If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + 7 = 912 Reorder the terms: 7 + s = 912 Solving 7 + s = 912 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + s = 912 + -7 Combine like terms: 7 + -7 = 0 0 + s = 912 + -7 s = 912 + -7 Combine like terms: 912 + -7 = 905 s = 905 Simplifying s = 905
| -50-3x=13-10x | | 7(x-6)=-28 | | 3(x+5)=18 | | 2x-4y=22 | | 6(a+1)=30 | | 8x-3=-51 | | 6y^2-10y=0 | | 2x^2-13x-45=0 | | n-7=14 | | n+34=54 | | n-13=18 | | 75-5x=31x+15 | | 6+11x=106+6 | | n-9=13 | | -1=-3r+2rp | | 4x+30=12x-58 | | n+36=52 | | n+18=24 | | 9x+7=5x+31 | | 14m=-3-8m^2 | | 4x+34=14x-56 | | 7x-16=47 | | 8x+2=58 | | -32-7x=9x+16 | | 7(h+3)+4=-2 | | -42rst+66r^2s-12rs^2t= | | 2x+10=-23-9x | | (Y+2)(y^2-3y-10)=0 | | 4x+19=8x-9 | | 113-4x=3x+15 | | 138-7x=29x+18 | | 3x+34=5x |